An Active-Reactive Power Coordinated Robust Optimization Method for Electricity Gas Interconnection Based Multiple Interval Uncertain - LIN Chaohua, ZHANG Junda, WU Rongfen, LIANG Haitian, WANG Qiuping, LIAO Xiaobing (Dianli jianshe)
[Objective] To accurately describe the impact of the volatility and randomness of the output power of new energy sources on the operation of an electricity-gas interconnected system and improve the robustness of its optimal operation， a robust optimization method based on multiple-interval uncertainty sets is proposed. [Methods] First， the traditional interval set of a distributed photovoltaic output is constructed， and then， a single-interval correlation uncertainty set is established considering the time correlation. Second， to solve the problems of poor robustness and large conservatism in the traditional set， the single-interval set is cut and divided to obtain a multi-interval correlation set. Furthermore， considering the energy conversion device， an active-reactive power coordinated robust optimization model based on the multi-interval uncertainty set is established for electricity-gas interconnection. [Results] The simulation results for the improved IEEE 33 node power grid and Belgium 20 node gas network interconnection system showed that the proposed method could reduce the conservatism and improve the robustness of the optimization results， thus proving the effectiveness of the proposed method. [Conclusions] The proposed active-reactive coordinated robust optimization method for an electricity-gas interconnected system based on the multiple interval uncertainty set can not only effectively deal with the challenges generated by the volatility of new energy sources but also improve the system’s robustness while reducing the conservatism. This method provides a new solution for the optimal operation of an interconnected electricity-gas system and is of great significance for promoting safe and economic operation of energy systems with access to a high proportion of new energy sources.